The Urgency of Certificate Ownership as Proof of Land Rights Ownership in Tempuran Village - Arafat, Zarisnov; Putri, Desty Fiana; Arinta, Devi Arviani; Hariri, Mochammad Sofyan; Nurmala, Nurmala; Nugraha, Safaat; Salu, Vera Kartika (PT. Hafasy Dwi Nawasena, 2024)
One of the villages in Karawang Regency is called Tempuran village, which has a population of ± 4,300 people consisting of 11 RTs, 5 RWs and four hamlets. 60% already have a certificate, and 40% only have a verbal Deed of Sale and Purchase. Tempuran village follows the implementation of PTSL, which priorities systematic, complete, fast, simple and affordable principles for the Tempuran village community. Some village communities already know about land title certificates but have not yet reached the stage of implementing them by the regulations governing them. In reality, land rights regarding legal certainty do not always correspond to what is expected. Implementation in the field often occurs when the community does not have/has not yet produced a certificate of land rights, even though the community has lived on the land for a long time. This research aims to determine the urgency of land certificates as proof of ownership of land rights and what steps must be taken to provide legal awareness to the people of Tempuran village to have land certificates. This research uses qualitative research. The approach method uses an empirical juridical approach. The Result of this study Land certificates have a very strong function as legal evidence in providing certainty and legal protection to the owner. By having a certificate, Tempuran villagers have a strong legal basis to defend their land rights, in accordance with applicable regulations. Counseling the community on the obligation to maintain land in accordance with the UUPA and updating land data is important to be carried out regularly to ensure the accuracy of land ownership information in Tempuran Village.